Performance of Postemergence Herbicides Applied at Different Carrier Volume Rates - Creech, Cody F.; Henry, Ryan S.; Werle, Rafael [UNESP]; Sandell, Lowell D.; Hewitt, Andrew J.; Kruger, Greg R. (Weed Sci Soc Amer, 2015)
POST weed control in soybean in the United States is difficult because weed resistance to herbicides has become more prominent. Herbicide applicators have grown accustomed to low carrier volume rates that are typical with glyphosate applications. These low carrier volumes are efficient for glyphosate applications and allow applicators to treat a large number of hectares in a timely manner. Alternative modes of action can require greater carrier volumes to effectively control weeds. Glyphosate, glufosinate, lactofen, fluazifop-P, and 2,4-D were evaluated in field and greenhouse studies using 47, 70, 94, 140, 187, and 281 L ha(-1) carrier volumes. Spray droplet size spectra for each herbicide and carrier volume combination were also measured and used to determine their impact on herbicide efficacy. Glyphosate efficacy was maximized using 70 to 94 L ha(-1) carrier volumes using droplets classified as medium. Glufosinate efficacy was maximized at 140 L ha(-1) and decreased as droplet diameter decreased. For 2,4-D applications, efficacy increased when using carrier volumes equal to or greater than 94 L ha(-1). Lactofen was most responsive to changes in carrier volume and performed best when applied in carrier volumes of at least 187 L ha(-1). Carrier volume had little impact on fluazifop-P efficacy in this study and efficacy decreased when used on taller plants. Based on these data, applicators should use greater carrier volumes when using contact herbicides in order to maximize herbicide efficacy.
Keywords: Droplet size; herbicide efficacy; nozzles; soybean herbicides; spray rate